Excess mortality after hip fracture in elderly persons from Europe and the USA: the CHANCES project. (17th January 2017) - Katsoulis, M.; Benetou, V.; Karapetyan, T.; Feskanich, D.; Grodstein, F.; Pettersson‐Kymmer, U.; Eriksson, S.; Wilsgaard, T.; Jørgensen, L.; Ahmed, L. A.; Schöttker, B.; Brenner, H.; et al.
Abstract: Background: Hip fractures are associated with diminished quality of life and survival especially amongst the elderly. Objective: All‐cause mortality after hip fracture was investigated to assess its magnitude. Methods: A total of 122 808 participants from eight cohorts in Europe and the USA were followed up for a mean of 12.6 years, accumulating 4273 incident hip fractures and 27 999 deaths. Incident hip fractures were assessed through telephone interviews/questionnaires or national inpatient/fracture registries, and causes of death were verified with death certificates. Cox proportional hazards models and the time‐dependent variable methodology were used to assess the association between hip fracture and mortality and its magnitude at different time intervals after the injury in each cohort. We obtained the effect estimates through a random‐effects meta‐analysis. Results: Hip fracture was positively associated with increased all‐cause mortality; the hazard ratio (HR) in the fully adjusted model was 2.12, 95% confidence interval (CI) 1.76–2.57, after adjusting for potential confounders. This association was stronger amongst men [HR: 2.39, 95% CI: 1.72–3.31] than amongst women [HR: 1.92, 95% CI: 1.54–2.39], although this difference was not significant. Mortality was higher during the first year after the hip fracture [HR: 2.78, 95% CI: 2.12–3.64], but it remained elevated without major fluctuations after longer time since hip fracture [HR (95% CI): 1.89 (1.50–2.37) after 1–4 years; 2.15 (1.81–2.55) after 4–8 years; 1.79 (1.57–2.05) after 8 or more years]. Conclusion: In this large population‐based sample of older persons across eight cohorts, hip fracture was associated with excess short‐ and long‐term all‐cause mortality in both sexes.